Development of Zn and Fe biofortified high yielding premium quality aromatic rice suitable for wet season in Bangladesh : Development of Zn and Fe biofortified rice - Ali, Liakat; Haque, M Moynul; Maniruzzaman, Sheikh; Ivy, Nasrin Akter (Annals of Bangladesh Agriculture, 2026)
The existing cultivars of aromatic rice are not sufficient to satisfy the demand for aromatic rice because of their limited yield potentials and environmental constraints. High yielding aromatic rice is a significant agricultural focus in Bangladesh due to its potential to enhance food security, economic growth, and export revenues. The research was instigated to develop high yielding, premium quality new aromatic rice variety to satisfy the present market demand. Therefore, single crosses were made and after confirmation of F1 s, generations were advanced through the pedigree selection method until the selection of several superior inbred lines. Among the selected lines, the proposed genotype (BU-103-23-5-3) was derived from ACC 34 X ACC 51 with better qualitative and quantitative attributes than the check variety (BRRI dhan70). The proposed genotype has the modern plant architecture, having tall but robust plant with an erect flag leaf, a long panicle with higher filled grain in addition to insects and diseases resistance. On an average, it requires 120-125 days to mature with a yield potential of 5.0 to 5.5 t ha-1, which is earlier and showed nearly 20 % higher yield than the check variety. It is recognized as long-slender, premium quality rice with 21.9 g of 1000-grain weight. Amylose and protein content of the polished rice are 26 and 7.56 %, respectively. The proposed genotype is Zn and Fe biofortified aromatic rice containing 23.6 ppm of Zn and 11 ppm of iron in the 11% polished rice. The newly developed genotype has satisfactorily passed the Proposed Variety Trial (PVT) conducted in ten locations during wet (Aman) season of 2023. Consecutively, the National Seed Board (NSB) approved the proposed genotype (BU-103-23-5-3) as GAU dhan 3 for commercial cultivation in the wet season in Bangladesh because of its significant benefits for food security, economic growth, and export revenues. Ann. Bangladesh Agric. 29(2): 125-140